IMPROVING STUDENTS' UNDERSTANDING IN PAI LEARNING THROUGH QUIZZ-BASED DIGITAL MEDIA AT SMAN 1 TANAH LUAS - Rafizal; Jalaluddin; Yusnaini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to improve students' understanding in Islamic Religious Education (PAI) learning through the use of Quizizz-based digital media at SMAN 1 Tanah Luas. The background of this study is based on the low level of involvement and understanding of some students in the PAI learning process, which is caused by the use of learning methods that are still conventional and less varied. This condition has an impact on low student learning motivation and less than optimal achievement of learning objectives. Along with the development of technology and the characteristics of students in the digital era, learning innovations are needed that are able to provide a more interesting, interactive learning atmosphere, and are in accordance with student needs. This study uses a quantitative approach with a quasi-experimental design to measure the effect of using Quizizz-based digital media on student understanding. The research subjects were grade X students of SMAN 1 Tanah Luas who were selected as the research sample. Data collection techniques were carried out through pretests and posttests to measure improvements in student learning outcomes, and supported by observation and documentation to obtain a comprehensive picture of the learning process. Quizizz media was used as a means of evaluation and reinforcement of Islamic Religious Education material, by presenting interactive questions that encourage active student participation in the learning process. The results of the study showed a significant increase in student understanding after the implementation of Quizizz-based digital media in Islamic Religious Education (PAI) learning. This was demonstrated by an increase in the average value of student learning outcomes as well as increased student enthusiasm and activeness during the learning process. The use of Quizizz not only helped students better understand Islamic Religious Education material but also created a fun and healthy competitive learning atmosphere. Thus, Quizizz-based digital media has proven effective in improving student understanding and presenting Islamic Religious Education learning that is more engaging, interactive, and relevant to the characteristics of learners in the digital era.